Integration of Small Farmers into Value Chains: Evidence from Eastern Europe and Central Asia - Jon H. Hanf; Taras Gagalyuk (Agricultural Value Chain, 2018)
The economic breakdown of the early transition process weighed heavily on food supply relationships in the Eastern European and Central Asian (EECA) countries. Small and medium-sized farm suppliers and processors suffered from lack of necessary production inputs whereas processors and retailers faced problems of insufficient quantity and quality of supplies. At the same time, changes in consumer demand as well as the accompanying entry of foreign investors in the retail and processing sectors necessitated significant and lengthy reforms and adjustments in the structure of food commodity chains to overcome these problems. Based on an extensive literature overview and a synthesis of five case studies conducted upon the assignment of Food and Agriculture Organization (FAO) of the United Nations, the current chapter demonstrates how small and mediumsized food processors manage to install effective procurement systems in weak institutional environments of EECA. The chapter also identifies the factors that drive small farmer-processor business linkages and their integration into national and international value chains in order to develop options for support and assistance.
Keywords: 330; Eastern Europe and Central Asia; farm assistance; food chain; processors; smallholders; vertical coordination